Whole-plant forage, grain or non-heading sorghum silages, cornlage, and feed flavor supplements for growing calves - Bolsen, K.; Ilg, H.; Hinds, M.; Hoover, J.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2010)
Four whole-plant silages produced in 1981 and 1982 were evaluated using 176 calves in two growing trials. Based on comparative rates and efficiencies of gain, feeding values were 115, 100, 78.5, and 62 for the cornlage, grain sorghum, forage sorghum, and non-heading sorghum silages, respectively. The poorer values for the forage and non-heading silages were due, in part, to low feed intakes. Rolling the grain and forage sorghum silages to break 85% to 95% of the kernels did not improve their value, and the good performance by calves suggests that the whole grain was well utilized.. A feed flavor supplement, Omniflavor, did not improve performance in trial 1 but did increase rates and efficiencies of gain in trial 2.
Keywords: Beef; Forage; Grain; Sorghum silages; Calves